2017
DOI: 10.2344/anpr-64-02-05
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Topical Anesthesia Using an Adhesive Patch and Anesthetic Solution

Abstract: We analyzed trigeminal somatosensory evoked potentials (TSEP) to the alveolar mucosa to investigate the efficacy of an amide local anesthetic, 2% lidocaine hydrochloride with 12.5 lg/mL epinephrine (Lido treatment) as a topical anesthetic. Eighteen consenting healthy adult volunteers were enrolled. A volume of 0.06 mL of Lido, 0.06 g of 20% benzocaine, or 0.06 mL of physiological saline (control) was instilled onto a hemostatic adhesive patch, which was then applied to the alveolar mucosa at the maxillary righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Lignocaine, which is used for infiltration anesthesia is an amide anesthetic. Kishimoto et al [ 34 ] compared the effects of lignocaine and benzocaine delivered through transmucosal patches based on trigeminal somatosensory evoked potentials. They observed that an amide anesthetic like lignocaine had similar efficacy to benzocaine when used as a topical anesthetic and concluded that 2% lidocaine with epinephrine used as a topical anesthetic in an adhesive patch was as potent as 20% benzocaine.…”
Section: Discussionmentioning
confidence: 99%
“…Lignocaine, which is used for infiltration anesthesia is an amide anesthetic. Kishimoto et al [ 34 ] compared the effects of lignocaine and benzocaine delivered through transmucosal patches based on trigeminal somatosensory evoked potentials. They observed that an amide anesthetic like lignocaine had similar efficacy to benzocaine when used as a topical anesthetic and concluded that 2% lidocaine with epinephrine used as a topical anesthetic in an adhesive patch was as potent as 20% benzocaine.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the 10% dose of lidocaine gives the same result as the 20% dose with mepivacaine [24] . Several authors have reported in the literature that, within the lidocaine patch presentation, the 5% presentation can significantly reduce the pain of needle injection more than the gel in children [25,26,27,28] .…”
Section: Dosages and Presentationsmentioning
confidence: 99%